Study protocol for a scoping review on rehabilitation scoping reviews. (September 2017) - Colquhoun, Heather L; Jesus, Tiago S; O'Brien, Kelly K; Tricco, Andrea C; Chui, Adora; Zarin, Wasifa; Lillie, Erin; Hitzig, Sander L; Straus, Sharon
Introduction: Scoping reviews are increasingly popular in rehabilitation. However, significant variability in scoping review conduct and reporting currently exists, limiting potential for the methodology to advance rehabilitation research, practice and policy. Our aim is to conduct a scoping review of rehabilitation scoping reviews in order to examine the current volume, yearly distribution, proportion, scope and methodological practices involved in the conduct of scoping reviews in rehabilitation. Key areas of methodological improvement will be described. Methods and analysis: We will undertake the review using the Arksey and O'Malley scoping review methodology. Our search will involve two phases. The first will combine a previously conducted scoping review of scoping reviews (not distinct to rehabilitation, with data current to July 2014) together with a rehabilitation keyword search in PubMed. Articles found in the first phase search will undergo a full text review. The second phase will include an update of the previously conducted scoping review of scoping reviews (July 2014 to current). This update will include the search of nine electronic databases, followed by title and abstract screening as well as a full text review. All screening and extraction will be performed independently by two authors. Articles will be included if they are scoping reviews within the field of rehabilitation. A consultation exercise with key targets will inform plans to improve rehabilitation scoping reviews. Ethics and dissemination: Ethics will be required for the consultation phase of our scoping review. Dissemination will include peer-reviewed publication and conferences in rehabilitation-specific contexts.